The Appeal of Panpsychism in Victorian Britain - Pinch, Adela (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2014)
This article argues that current trends in the humanities that embrace panpsychism, vibrant matter, object-oriented ontologies, and extended or dispersed conceptions of consciousness, could benefit from an examination of Victorian debates about panpsychism. The article does this by exploring panpsychism’s relation to Victorian theories of evolution, late nineteenth-century idealism, and above all to conversations about desire, will, and consciousness. The article suggests further that understanding Victorian panpsychism can illuminate key aspects of Victorian aesthetics: detail, pattern, and dispersal. Authors discussed include philosophers W.K. Clifford, William James, and May Sinclair; the article then turns to Victorian translations of Lucretius, the poetry of Swinburne, the designs of William Morris, and the literary theory of Vernon Lee.